Clinical significance of DNA methylation in chronic lymphocytic leukemia patients: results from 3 UK clinical trials - Wojdacz, Tomasz K.; Amarasinghe, Harindra E.; Kadalayil, Latha; Beattie, Alice; Forster, Jade; Blakemore, Stuart J.; Parker, Helen; Bryant, Dean; Larrayoz, Marta; Clifford, Ruth; Robbe, Pauline; Davis, Zadie A.; et al. (AMER SOC HEMATOLOGY, 2019)
Chronic lymphocytic leukemia patients with mutated immunoglobulin heavy-chain genes (IGHV-M), particularly those lacking poor-risk genomic lesions, often respond well to chemo immunotherapy (CIT). DNA methylation profiling can subdivide early-stage patients into naive B-cell-like CLL (n-CLL), memory B-cell-like CLL (m-CLL), and intermediate CLL (i-CLL), with differing times to first treatment and overall survival. However, whether DNA methylation can identify patients destined to respond favorably to CIT has not been ascertained. We classified treatment-naive patients (n = 605) from 3 UK chemo and CIT clinical trials into the 3 epigenetic subgroups, using pyrosequencing and microarray analysis, and performed expansive survival analysis. The n-CLL, i-CLL, and m-CLL signatures were found in 80% (n = 245/305), 17% (53/305), and 2% (7/305) of IGHV-unmutated (IGHV-U) cases, respectively, and in 9%, (19/216), 50% (108/216), and 41% (89/216) of IGHV-M cases, respectively. Multivariate Cox proportional analysis identified m-CLL as an independent prognostic factor for overall survival (hazard ratio [HR], 0.46; 95% confidence interval [CI], 0.24-0.87; P = .018) in CLL4, and for progression-free survival (HR, 0.25; 95% CI, 0.10-0.57; P = .002) in ARCTIC and ADMIRE patients. The analysis of epigenetic subgroups in patients entered into 3 first-line UK CLL trials identifies m-CLL as an independent marker of prolonged survival and may aid in the identification of patients destined to demonstrate prolonged survival after CIT.